Vírus Rábico em célula McCoy - Parte III (Purificação) - L. Nogueira, Yeda; M. Souza Felippe, Julia (Revista do Instituto Adolfo Lutz, 1996)
During this work Sokol's classical method, slightly modified, was used in order to obtain lhe purified fraction of rabies virus. A filtration in Sephadex G-50 column took place followed by another filtration in Sephadex G75, eliminating the enzimatic treatment with DNase and RNase. The elution in Sephadex G-50 separated two peaks with activity in 280nm (Absorbance). Peak I has separed a bovine albumine serum and Peak II has separated rnost of the viral fraction purified, free of such eontaminats as serum or eellular proteins. Peak I was submitted to a saecharose gradient clumping ali viral particles components and they were bioehemically eharaeterized throughout the electrophoretic separation in poliaerylamide gel SDS-PAGE and immunogcnically throughout crossed immunoelectrophoresis. Crossed immunoelectrophoresis was used to follow all the purification process, allowing the observation of which fraetions were eliminated in each step of the process. On the other hand, two advantages could be obtained when the bovine albumine serum was eliminated in second filtration through the Sephadex G-50 and when erossed immunocletrophorcsis technique allowed a complete peer-view of the processo This aproach is very interesting when a large scale produetion process of purified antigen is involved for it allows the control of the purity degree and the attainment of a good quality control of the product.